Analisis Nilai Perjuangan dalam Puisi "Diponegoro" Karya Chairil Anwar - Taufiq Hidayat; Akhmad Fatoni (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study examines Chairil Anwar's poem "Diponegoro" from the perspective of literary sociology, focusing on the analysis of the values ​​of struggle contained therein. This poem depicts the figure of Prince Diponegoro as a symbol of resistance against colonialism, which reflects the spirit of the Indonesian people's struggle during the colonial period. Through the approach of literary sociology according to Wellek and Warren. This analysis also pays attention to how Chairil Anwar uses the figure of Diponegoro to convey messages about courage, sacrifice, and steadfastness in fighting oppression. The results of the study show that the poem "Diponegoro" not only functions as an individual expression of the author, but also as a form of representation of the collective aspirations of the people who are fighting for independence. Thus, the values ​​of struggle in this poem have strong social relevance, illustrating the relationship between literary works and the social dynamics around them.